Case Report: Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with SARS-CoV-2 with Coronary Involvement - Carraro, Mariana; Rodrigues, Bárbara Rocha; Jr, Virmondes Rodrigues (Archives of Clinical and Biomedical Research, 2020)
In the face of the emergence of COVID-19, the multisystem inflammatory syndrome in children (MIS-C), associated with SARS-CoV-2, has shown an increase of cases worldwide among the pediatric population, with clinical presentation and evolution similar to Kawasaki disease. Despite the similarities, these cases present clinical and laboratory particularities that make it necessary to increase the description of similar cases around the world, in order to reach a consensus on this new disease in the future. Here, we bring a Brazilian case, followed up in the countryside of Minas Gerais, in which a cardiovascular involvement was found but with a benign evolution.